2014
DOI: 10.1155/2014/875861
|View full text |Cite
|
Sign up to set email alerts
|

CAT, GPX1, MnSOD, GSTM1, GSTT1, andGSTP1Genetic Polymorphisms in Chronic Myeloid Leukemia: A Case-Control Study

Abstract: Oxidative damage at the DNA level may be promoted by high levels of reactive oxygen species (ROS), leading to genomic instability and increased neoplastic risk. Superoxide dismutase (SOD), glutathione peroxidase (GPX), and catalase (CAT) enzymes are implicated in the prevention of DNA damage by ROS. The aim of the study was to investigate the relationships between CAT C262T, GPX1 Pro198Leu, MnSOD Ala16Val, GSTM1, GSTT1, and GSTP1 Ile105Val polymorphisms and the risk of CML. No association was observed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
42
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 19 publications
11
42
3
2
Order By: Relevance
“…In our study, a significant relationship was observed between risk to develop CML and GSTM1 and GSTP1 (on additive scale), indicating a meaningful association of these genes on CML susceptibility. These findings are consistent with previous association studies that demonstrated GSTM1/null and GSTP1/GG are predisposing factors to CML susceptibility (Bănescu et al, ; Kagita Sailaja, Rao, Rao, & Vishnupriya, ). Similar results with our findings were clearly described regarding increased risk of CML for the GSTM1/null genotype by Bhat et al (), Lordelo et al () and Al‐Achkar et al ().…”
Section: Discussionsupporting
confidence: 93%
“…In our study, a significant relationship was observed between risk to develop CML and GSTM1 and GSTP1 (on additive scale), indicating a meaningful association of these genes on CML susceptibility. These findings are consistent with previous association studies that demonstrated GSTM1/null and GSTP1/GG are predisposing factors to CML susceptibility (Bănescu et al, ; Kagita Sailaja, Rao, Rao, & Vishnupriya, ). Similar results with our findings were clearly described regarding increased risk of CML for the GSTM1/null genotype by Bhat et al (), Lordelo et al () and Al‐Achkar et al ().…”
Section: Discussionsupporting
confidence: 93%
“…49 articles were excluded: 3 were reviews; 9 were conference abstracts; 4 were related to other SNPs of the CAT gene; 11 did not report extractable data; 22 were irrelevant papers. Finally, a total of 33 articles678111215161718192021222324252627282930313233343536373839404142 published from 2005 to 2015met the inclusion criteria and were included in our meta-analysis. There were 27 publications678111215161718192123242526272829303133343537383940 regarding susceptibility analysis, which involved 35 case-control or cohort studies with 15531 cancer patients and 41816 controls, while 8 publications620222932364142 contained the survival data.…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis of the 27 articles678111215161718192123242526272829303133343537383940 with 35 case-control or cohort studies suggested there was a positive correlation between the CAT C262T polymorphism and cancer risk (TT + CT vs CC: OR = 1.05, 95%CI = 1.00–1.10, P = 0.036; TT vs CT + CC: OR = 1.18, 95%CI = 1.08–1.29, P < 0.001; TT vs CC: OR = 1.22, 95%CI = 1.10–1.35, P < 0.001; T vs C: OR = 1.07, 95%CI = 1.03–1.11, P = 0.001 Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…Glutathione S-transferases (GSTs) are a group of genes, the polymorphisms of which have been reported to be also associated with an increased risk for Diabetes Mellitus (DM) [2], malignant diseases [3], and diabetic retinopathy [4].…”
mentioning
confidence: 99%
“…Glutathione S-transferases (GSTs) represent a family of multifunctional phase II isoenzymes known for their capacity of catalyzing the conjugation of reduced glutathione with a large variety of electrophilic compounds, including carcinogenic agents and products derived from oxidative stress; it has a major role in neutralizing reactive oxygen species (ROS), and it is part of the cellular protection and detoxifying mechanisms, hence the important antioxidant role [3]. Three of these polymorphisms, namely GSTM1, GSTT1, and GSTP1 have raised special interest, and therefore have been more intensively studied.…”
mentioning
confidence: 99%